Campur Kode Bahasa Indonesia–Inggris dalam Tuturan Generasi Z di Media Sosial: Kajian Sosiolinguistik terhadap Fenomena “Bahasa Jaksel” - Try Widya Andini; Qesya Balqis Lubis; Naina Ikhdina Hapiz; Zaskia Putri Andari; Shintya Akrima; Afriani Sasmitha; Ayu Nadira Wulandari (CV. SINAR HOWUHOWU, 2026)
The phenomenon of code-mixing between Indonesian and English has become increasingly prevalent among Generation Z, particularly in social media communication. This study aims to examine the forms, causal factors, and impacts of code-mixing in youth speech, especially the variety known as “Jaksel language.” This research employs a descriptive qualitative approach, with data collected from social media content such as TikTok and YouTube. Data collection techniques include observation, documentation, and note-taking, while data analysis is conducted through data reduction, classification, and interpretation based on a sociolinguistic framework. The findings reveal that the dominant forms of code-mixing involve the insertion of English elements at the levels of words, phrases, and clauses, with Indonesian remaining the primary language. The factors influencing this phenomenon include bilingualism, the prestige of English, communicative efficiency, and the influence of social media and global culture. Furthermore, code-mixing functions as a means of self-expression and a marker of social identity among urban youth. In terms of impact, code-mixing has positive implications in enriching vocabulary through integration processes, but it also has the potential to cause interference if it affects the structure of the Indonesian language. Socially, this phenomenon can strengthen group solidarity while also creating exclusivity in communication. Therefore, code-mixing is a complex and multidimensional linguistic phenomenon that reflects the dynamic nature of language in a bilingual digital society.